(Re)searching (Trans-Multi)Culturally Responsive Curricular Conversations - Raisinghani, Latika (Journal of the Canadian Association for Curriculum Studies, 2016)
Haunted by the regurgitating moments of schooling experienced by myself and my students in multiple cultural contexts, in this paper, I attempt to initiate a provocative dialogue regarding the kinds of conversations we should have to bring “education” into today’s culturally diverse classrooms. By sharing the current dilemmas encountered by many students in contemporary schooling, specifically in science and mathematics classrooms, I argue for the creation and enactment of a (trans-multi)culturally responsive curriculum. Drawing on Aoki’s inspirited rhizomatic curriculum, Pinar’s currere as a complicated conversation, along with Schwab’s deliberated practice of engaging curricular commonplaces in a dialogue, I propose a (trans-multi)culturally responsive curricular framework as one way to invite teachers to engage deliberatively in a complicated conversation that could broaden their understandings of culturally responsive education in today’s classrooms.